An effective network reconfiguration approach of radial distribution system for loss minimization and voltage profile improvement - Surender Reddy Salkuti; Neelakanteshwar Rao Battu (Institute of Advanced Engineering and Science, 2021)
Distribution system represents a crucial portion of power system as it is the connection between the bulk power transmission network and the customers connected at load point. Distribution networks are increasing in size and are spread too far. Low reactance to resistance ratio and large size of network leads to higher power losses in lines and low node voltage at customer end. High power losses reduce the efficiency and affect the economy. Therefore, in this paper an algorithm for reconfiguration of distribution system for loss reduction and voltage profile enhancement is proposed. The proposed reconfiguration approach has been applied to 16 bus radial distribution system (RDS).